What we don't need to prove but need to do in multidisciplinary treatment and care in Huntington's disease: a position paper - Mühlbӓck, Alzbeta; van Walsem, Marleen; Nance, Martha; Arnesen, Astri; Page, Kirsty; Fisher, Alexandra; van Kampen, Manon; Nuzzi, Angela; Limpert, Roy; Fossmo, Hanne Ludt; Cruickshank, Travis; Veenhuizen, Ruth; et al. (Orphanet journal of rare diseases, 2023)
BACKGROUND: Huntington's disease is a complex neurodegenerative hereditary disease with symptoms in all domains of a person's functioning. It begins after a healthy start in life and leads through the relentless progression over many years to complete care dependency and finally death. To date, the disease is incurable. The long progressive complex nature of the disease demands multiple disciplines for treatment and care of patient and family. These health care providers need inter- and multidisciplinary collaboration to persevere and be efficacious in this devastating disease trajectory. DISCUSSION: The position paper outlines current knowledge and experience alongside the experience and consensus of a recognised group of HD multidisciplinary experts. Additionally the patient's voice is clear and calls for health care providers with a holistic view on patient and family. Building long-term trust is a cornerstone of the network around the patient. This paper describes a managed care network comprising all the needed professionals and services. In the health care system, the role of a central coordinator or case manager is of key importance but lacks an appropriate guideline. Other disciplines currently without guidelines are general practitioners, nurses, psychologists, and social workers. Guidelines for neurologists, psychiatrists, geneticists, occupational therapists, speech and language therapists, physiotherapists, dieticians, and dentists are being discussed. Apart from all these profession-specific guidelines, distinctive inter- and multidisciplinary collaboration requirements must be met. CONCLUSIONS AND RECOMMENDATIONS: The complex nature of Huntington's disease demands multidisciplinary treatment and care endorsed by international regulations and the lay association. Available guidelines as reviewed in this paper should be used, made available by a central body, and updated every 3-5 years. Time needs to be invested in developing missing guidelines but the lack of this 'proof' should not prevent the 'doing' of good care.
Keywords: Huntington’s disease; Managed care network; Multidisciplinary treatment; konsensus; Guidelines; Huntington Disease; Consensus; Humans; Health Personnel; Care; Position paper; lidé; zdravotnický personál; Delivery of Health Care; Case manager; Huntingtonova nemoc; Interdisciplinary team; poskytování zdravotní péče